CqHKT1 and CqSOS1 mediate genotype-dependent Na+ exclusion under high salinity conditions in quinoa - Kobayashi, Yasufumi; Sugita, Ryohei; Fujita, Miki; Yasui, Yasuo; Murata, Yoshinori; Ogata, Takuya; Nagatoshi, Yukari; Fujita, Yasunari (Frontiers in Plant Science, 2025)
Salinity threatens crop production worldwide, and salinized areas are steadily increasing. As most crops are sensitive to salt, there is a need to improve the salt tolerance of major crops and promote the cultivation of under-utilized salt-tolerant crops. Quinoa, a pseudocereal and leafy vegetable from the Andean region of South America, is highly salt-tolerant, thrives in marginal environments, and has excellent nutritional properties. Research has often focused on epidermal bladder cells, a feature of quinoa thought to contribute to salt tolerance; however, recent evidence suggests that these cells are not directly involved. The salt tolerance mechanism in quinoa remains unclear. Here, we show genotype-dependent differences in Na+ and K+ accumulation mechanisms using representative 18 lines of three genotypes by focusing on young quinoa seedlings at a stage without epidermal bladder cells. High salinity (600 mM NaCl) did not affect the early growth of all three quinoa genotypes. Under high salinity conditions, lowland quinoa lines tended to accumulate more Na+ in their aerial parts than highland lines did. By contrast, K+ accumulation was slightly reduced in the aerial parts but significantly decreased in the roots of all the genotypes. Resequencing of 18 quinoa lines supports the notion that genotype determines aboveground Na+ uptake and gene expression in response to high salinity. Using virus-induced gene silencing, we further demonstrated that CqHKT1 and CqSOS1 mediate Na+ exclusion in quinoa. These findings provide insight into salt tolerance mechanisms, serving as a basis for improving crop production under high salinity conditions.